An Increased Risk of Reversible Dementia May Occur After Zolpidem Derivative Use in the Elderly Population: A Population-Based Case-Control Study. Issue 17 (May 2015) - Shih, Hsin-I.; Lin, Che-Chen; Tu, Yi-Fang; Chang, Chia-Ming; Hsu, Hsiang-Chin; Chi, Chih-Hsien; Kao, Chia-Hung
Abstract : Abstract: We evaluate the effects of zolpidem use to develop dementia or Alzheimer disease from the Taiwan National Health Insurance Research Database (NHIRD). A retrospective population-based nested case–control study. Newly diagnosed dementia patients 65 years and older and controls were sampled. A total of 8406 dementia and 16, 812 control subjects were enrolled from Taiwan NHIRD during 2006 to 2010. The relationships between zolpidem use and dementia were measured using odds and adjusted odds ratios. The relationship between the average cumulative doses for zolpidem and dementia was also analyzed. Zolpidem alone or with other underlying diseases, such as hypertension, diabetes, and stroke, was significantly associated with dementia after controlling for potential confounders, such as age, sex, coronary artery disease, diabetes, anti-hypertension drugs, stroke, anticholesterol statin drugs, depression, anxiety, benzodiazepine, anti-psychotic, and anti-depressant agents' use (Adjusted OR = 1.33, 95% CI 1.24–1.41). Zolpidem use also has significant dose–response effects for most of the types of dementia. In patient with Alzheimer diseases, the effects of zolpidem among patients with Alzheimer's disease remained obscure. The adjusted OR for patients whose cumulative exposure doses were between 170 and 819 mg/year (adjusted OR: 1.65, 95% CI 1.08–2.51, P = 0.0199) was significant; however, the effects for lower and higher cumulative dose were not significant. Zolpidem used might be associated with increased risk for dementia in elderly population. Increased accumulative dose might have higher risk to develop dementia, especially in patients with underlying diseases such as hypertension, diabetes, and stroke.